Variety Types of Natural Food Fish Usage in The Growth of Super Red Arowana Fish (Scleropages Formosus) - Amyda Suryati Panjaitan; Fitriska Hapsari; Margono Margono; Himmah Al-Qoyyimah (Eduvest - Journal of Universal Studies, 2023)
This study aims to determine the effect of giving several types of natural feed and evaluate the best type of feed for thebody length of super red arowana fish (Scleropages formosus). This study used the Complete Randomized Design (RAL) method with 3 treatments and 3 repeats with 3 types of natural feed, namely crickets (A), Hong Kong caterpillars (B), and white shrimp (C). The maintenance of super red arowana fish is carried out for 70 days with a frequency of feeding three times a day and given satiation (ad satiation). The results showed that the feeding of crickets for super red arowana fish gave the highest length of 0.84±0.08 cm, the highest specific growth rate of 6.00±0.59%, and the survival rate (SR) at the end of the study was 100%. The results of measuring water quality parameters, namely temperatures of 28.7° C -30.4 °C, pH 7.97-8.14, and dissolved oxygen 4.6-5.4 mg.l⁻¹, are in the optimal range for the maintenance of super red arowana fish.